2020
DOI: 10.2754/avb202089040349
|View full text |Cite
|
Sign up to set email alerts
|

A multiannual survey of cadmium content in pig tissues collected in the Czech Republic during the years 2015–2019

Abstract: The assessment of cadmium content in the muscle, liver and kidneys of fattening pigs and sows was conducted in the Czech Republic during the period of 2015–2019. The samples were collected from a total of 32 sows and 210 fattening pigs. The mean cadmium content in the livers and kidneys of all sows was 0.102 ± 0.010 and 0.361 ± 0.032 mg·kg-1, respectively. The mean cadmium content in the livers and kidneys of all fattening pigs was 0.028 ± 0.001 and 0.141 ± 0.005 mg·kg-1, respectively. The maximum residual lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Except for Al, Cr, Ni, and Sn, all the measured TMM levels were significantly higher ( p < 0.01) and more widely distributed in liver compared to muscle samples ( Figure 1 ). This scattered distribution implies the existence of a high inter-animal variability among pigs which, besides deriving from feed, environment, and farming practices, may be linked to individual genetic factors [ 40 , 41 ]. As expected, Cu, Fe, and Zn were the prominent elements in both tissues, where they exert biologically important functions and are regulated by homeostatic processes [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for Al, Cr, Ni, and Sn, all the measured TMM levels were significantly higher ( p < 0.01) and more widely distributed in liver compared to muscle samples ( Figure 1 ). This scattered distribution implies the existence of a high inter-animal variability among pigs which, besides deriving from feed, environment, and farming practices, may be linked to individual genetic factors [ 40 , 41 ]. As expected, Cu, Fe, and Zn were the prominent elements in both tissues, where they exert biologically important functions and are regulated by homeostatic processes [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cd showed a 60-fold higher median concentration in livers ( Figure 2 ). In this context, it was demonstrated that feed supplements containing Fe, Zn, Cu, and Ca may significantly increase the rate of absorption and accumulation of Cd in livestock tissues, hence suggesting that the main source of Cd for pigs is feed itself [ 8 , 41 ]. Median concentrations of i As and i Hg in muscles (0.0064 and 0.00088 mg kg −1 , respectively) were significantly lower compared to data reported by EFSA in livestock meat [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, based on the valid legislation, it is obligatory to monitor OTA (as well as other nephrotoxic substances, e.g. mercury and cadmium) in certain foods and feeds (Commission Recommendation 2006;Commission Regulation 2006;Svoboda et al 2020;Svoboda et al 2021).…”
mentioning
confidence: 99%
“…In both cases, however, organ-specific distribution and abundance occurs in particular structures. The accumulation of heavy metals in some tissues can also provide a persistent source of low dose toxicity through constant intracellular bioavailability of the toxic metal (Ariza et al 1999;Fowler 1998;Svoboda et al 2020).…”
mentioning
confidence: 99%